1980
DOI: 10.1515/mamm.1980.44.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Cycles de reproduction des microchiroptères troglophiles du nord-est du Gabon

Abstract: Cycles de reproduction des microchiropteres troglophiles du nord-est du Gabonpar A. BROSSET et H. SAINT GIRONS Sous 1'cquateur (O°4' N 7 ), unc etude de terrain poursuivie pendant 14 ans montre que le cycle de reproduction des Microchiropteres troglophiles du nord-est du Gabon est monoestrien saisonnicr. Toutes les iemelles mettcnt bas une fois par an la meme date. L'etude histologique precise que le cycle sexuel des males est synchronise avec celui des femellcs qui ne presentent ni ovulation, ni implantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 3 publications
2
36
1
1
Order By: Relevance
“…The spatial scale of their movements remains to be determined, as does whether their movements represent true seasonal migrations, or nomadism. In any case, previous characterizations of these species as 'resident' (Fry et al, 1988;Dowsett & Dowsett-Lemaire, 1993;Christy, 1994) with fixed home ranges of 150 to 'several hundred' hectares (Brosset & Erard, 1986) are not supported by the data. A smaller species, fistulator, does not track fruit resources (at least, not on the same scale as its congeners) and does not exhibit between-site synchrony in abundance, indicating that it is relatively sedentary.…”
Section: Resource Tracking and Large-scale Movementscontrasting
confidence: 61%
“…The spatial scale of their movements remains to be determined, as does whether their movements represent true seasonal migrations, or nomadism. In any case, previous characterizations of these species as 'resident' (Fry et al, 1988;Dowsett & Dowsett-Lemaire, 1993;Christy, 1994) with fixed home ranges of 150 to 'several hundred' hectares (Brosset & Erard, 1986) are not supported by the data. A smaller species, fistulator, does not track fruit resources (at least, not on the same scale as its congeners) and does not exhibit between-site synchrony in abundance, indicating that it is relatively sedentary.…”
Section: Resource Tracking and Large-scale Movementscontrasting
confidence: 61%
“…Forbes-Watson (1975) mentions an observation of this species by C. Erard in Gabon, and on the basis of this Louette (1981) suggested that it could occur in Cameroon. Erard himself does not mention the observation in two subsequent works (Brosset andErard 1986, Erard 1990), so it is assumed here that the record was not confirmed and that the species is indeed an Upper Guinea forest endemic.…”
Section: Nimba Flycatcher Vulnerablementioning
confidence: 86%
“…It has been recorded in CAR (Carroll 1988, Keith et al 1992). An inhabitant of both primary and secondary forest, it often joins mixed-species flocks (Brosset and Erard 1986, T.B.S. unpubl.…”
Section: Resultsmentioning
confidence: 99%
“…An inhabitant of lowland dense thickets, rainforest, riverine and transitional montane forest, it commonly follows ant columns (Brosset and Erard 1986).…”
Section: Resultsmentioning
confidence: 99%